2021
DOI: 10.1001/jamaoncol.2021.1119
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of Screening Endoscopy for Colorectal Cancer in Older Adults

Abstract: Colorectal cancer is not only one of the most common, but also one of the most preventable cancers globally. Screening for colorectal cancer has been associated with reduced diseasespecific mortality through detection of cancer at earlier stages, as well as through detection and removal of its precursor lesions.While most professional guidelines recommend routine screening of asymptomatic adults older than 50 years for colorectal cancer, there is disagreement on the age to stop screening. For example, the US P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Given the elevated risk of colonoscopy harms among older adults, including post colonoscopy bleeding, 7 several experts have called for increased consideration of stool testing among adults aged 76 years and older. 7,8 Our study found stool testing was less common than colonoscopy among older Americans in 2019, and CT colonography and flexible sigmoidoscopy were rarely used. These patterns by test type mirror 2018 test use patterns reported for US adults aged 50-75 years.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Given the elevated risk of colonoscopy harms among older adults, including post colonoscopy bleeding, 7 several experts have called for increased consideration of stool testing among adults aged 76 years and older. 7,8 Our study found stool testing was less common than colonoscopy among older Americans in 2019, and CT colonography and flexible sigmoidoscopy were rarely used. These patterns by test type mirror 2018 test use patterns reported for US adults aged 50-75 years.…”
Section: Discussionmentioning
confidence: 89%
“…The AG cases have recently had substantial growth in use by non-MD students 8 especially by Doctor of Osteopathy (DO) students, IM and FM residents, Geriatrics Fellows, and NP and PA students. This letter describes the extent and pattern of use of AG cases and the level of satisfaction stratified by discipline, to inform the growth of AG to be inclusive of the various HP students' professional competencies.…”
Section: Introductionmentioning
confidence: 99%
“…As the program is implemented, screening strategies for younger populations can be further optimized. Similarly, for the elderly population, the incidence of adverse events from colonoscopy increases, and the bene ts of screening are controversial, which may require more personalized approaches 25 .…”
Section: Discussionmentioning
confidence: 99%